Robust Fuzzy Adaptive Control with MRAC Configuration for a Class of Fractional Order Uncertain Linear Systems - Bachir Bourouba; Samir Ladaci; Rachid Illoul (International Journal of Robotics and Control Systems, 2021)
This paper investigates a novel robust fractional adaptive control design for a class of fractional-order uncertain linear systems. Based on the Model Reference Adaptive Control (MRAC) configuration, the objective of the proposed controller is to ensure the output of the controlled plant to track the output of a given reference model system, while maintaining the overall closed-loop stability despite external disturbances and model uncertainties. An adaptive fuzzy logic controller is employed to eliminate unknown dynamics and disturbance. Lyapunov stability analysis demonstrates and verifies the desired fractional adaptive control system stability and tracking performance. Numerical simulation results illustrate the efficiency of the proposed adaptive fuzzy control strategy to deal with uncertain and disturbed fractional-order linear systems.